Adesão a vacinação contra o Papilomavírus Humano em usuários de unidades básicas de saúde do município de Ponta Grossa-PR e fatores associados - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
INTRODUCTION: Human Papillomavirus (HPV) infection is the most prevalent sexually transmitted infection in the world. Viruses from this family harbor significant human carcinogens. The HPV vaccine is one of the most effective interventions for preventing HPV-related complications. In Brazil, HPV vaccination was incorporated into the National Immunization Program in 2014. Despite the proven efficacy and safety of the vaccine, adherence is below the recommended target. OBJECTIVES: To assess adherence to HPV vaccination among eligible children and adolescents in Basic Health Units in the municipality of Ponta Grossa, PR, and associated factors. METHODOLOGY: This is a cross-sectional observational study conducted through interviews with parents of children and adolescents from 10 basic health units in Ponta Grossa/PR, eligible for HPV vaccination between 2017-2022. The questionnaire covered socioeconomic profile, knowledge about HPV and its vaccine, adherence, and barriers to HPV vaccination. RESULTS: A total of 412 interviews were conducted. The reported adherence to the complete HPV vaccine schedule (2 and 3 doses) was 50.58% among girls and 45.98% among boys. Adherence to a single dose of the vaccine was close to 80%. There was an association between age, gender, and informant's education level with the outcome. Participants with greater knowledge about HPV and its vaccine had higher vaccination rates. Most respondents believe the vaccine is safe and that HPV vaccination does not encourage early sexual activity. Among the respondents, 93.2% reported that HPV vaccination would be facilitated if carried out in schools, and 83.74% indicated a need for greater in formation dissemination about HPV. CONCLUSION: Adherence to the complete HPV vaccine schedule among boys and girls in the municipality of Ponta Grossa/PR, is below the established target and below the rates found in the state of Paraná. Factors such as knowledge gaps, especially regarding the association between HPV and cervical cancer, and concerns about vaccine safety may contribute to lower vaccination rates. Strategies to improve vaccine coverage should focus on increasing awareness, providing accurate information, and leveraging schools and healthcare professionals to promote and administer the vaccine effectively, thus reducing the impact of the virus on public health.
Keywords: Papillomavirus Humano HPV; Neoplasias do Colo do Útero; Vacinação; Cobertura Vacinal; Vacinas; Human Papillomavirus HPV; Uterine Cervical Neoplasms; Vaccination; Vaccine Coverage; Vaccines; CNPQ::CIENCIAS DA SAUDE